2020
DOI: 10.1111/pin.12913
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mTOR pathway expression in lymphatic malformation and related diseases

Abstract: The mammalian target of rapamycin (mTOR) inhibitor sirolimus is an effective treatment for difficult‐to‐treat lymphatic anomalies. However, little is known about the expression of mTOR pathway components in lymphatic anomalies. Here we investigated the expression pattern of mTOR pathway components and their phosphorylated forms (mTOR, p‐mTOR, 4EBP1, p‐4EBP1, S6K1 and p‐S6K1) in normal lymphatic vessels and lymphatic anomalies using immunohistochemistry. We studied 18 patients of lymphatic anomalies, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 31 publications
1
18
0
1
Order By: Relevance
“…11 Mammalian target of rapamycin (mTOR) is downstream of PI3K/AKT/mTOR pathway and it is proved that mTOR was detected in all lymphatic anomalies but not in normal lymphatics. 12 This evidence supports the therapeutic potential of the mTOR inhibitor sirolimus in LMs. The first report on the successful use of sirolimus as an antiangiogenetic agent was published in 2010.…”
Section: Introductionsupporting
confidence: 68%
“…11 Mammalian target of rapamycin (mTOR) is downstream of PI3K/AKT/mTOR pathway and it is proved that mTOR was detected in all lymphatic anomalies but not in normal lymphatics. 12 This evidence supports the therapeutic potential of the mTOR inhibitor sirolimus in LMs. The first report on the successful use of sirolimus as an antiangiogenetic agent was published in 2010.…”
Section: Introductionsupporting
confidence: 68%
“…Previous studies demonstrated that p-S6K1 was not detected in non-neoplastic fibrous tissue and adipose tissue [ 16 , 17 ], besides p-S6K1 showed sporadic expression in normal vessels [ 18 , 19 ]. Furthermore, both p-AKT and p-4EBP1 were not detected in non-neoplastic vessels, fibrous tissue and adipose tissue [ 16 , 17 , 19 21 ]. Thus, PI3K/AKT/mTOR pathway in mesenchymal malformation of FAVA is activated compared to that in normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they concluded that lymphangiogenesis is a valuable predictive biomarker for the therapeutic response to sirolimus in children with LM [ 32 ]. Hori et al [ 42 ] analyzed the activation of the mTOR pathway in a subset of lymphatic anomalies in vivo and demonstrated that normal lymphatic vessels expressed neither mTOR nor its phosphorylated form p‐mTOR. In contrast to normal lymphatic vessels, endothelial cells of LM, kaposiform lymphangiomatosis and kaposiform hemangioendothelioma expressed mTOR.…”
Section: Discussionmentioning
confidence: 99%